Thermoplastic Starch Biocomposite Produced from Corn (Zea mays): Comparison of Plasticizers Effects on Mechanical Properties - Odugbose, B. D.; Adefisan, O. O.; Adeyemi, H. O.; Opafola, O. T.; Olatunde, O. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
The excessive reliance on plastic materials made from fossil-fuel based and its ineffective waste management leads to environmental pollution due to their non-biodegradable nature. This study examined the production and testing of bio-composites from Gmelina Arborea wastes and thermoplastic starches as a polymer matrix. Particles of G. Arborea sawdust were obtained from a local sawmill while dry powdered corn starches were sourced from the chemicals market, Ojota, Lagos, Nigeria. Bio-composites were produced by mixing 40 g of corn starch, glycerol/sorbitol, and fractions of prepared G. Arborea (650µm particle sizes) fibre at 0 to 20% (wt/wt of fibre to polymer matrix) were added. The slurries were poured into a mould in accordance with ASTM D638 for tensile strength test samples. The results revealed that the thermoplastic starches, particle sizes, plasticizers, and wood fibre loading significantly affected the tensile strengths, tensile modulus, elongation at break of the bio-composites. Composites produced exhibited tensile strengths values range of 0.35 to 1.75 MPa, modulus of elasticity of 3.10 to 22 MPa, while there was a gradual reduction in elongation at break with a range of 127.4% to 111%. Sorbitol-corn starch generally recorded higher tensile properties of between 1.65 to 1.75 MPa tensile strength than those produced with glycerol plasticizer which ranged between 0.35 to 0.45 MPa as fibre loading increases. It is clear that sorbitol-plasticized bio-composite gives higher values in mechanical strengths when compared to that produced from glycerol.